Pictionary Game: A Teaching and Learning Method to Enhance Students’ Vocabulary - Lambok Hermanto Sihombing (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
Early childhood is the most critical stage for children in developing their brains. One of the ways to develop children's brains is through learning language. English is one of among recommended languages to learn. At an early age, acquiring new words is important to enabling the children to speak English or write English sentences. There are lots of fun teaching and learning methods to improve students' vocabulary. One of them is the Pictionary game. This study aims to analyze how the Pictionary game could be used as an alternative to enhance students' vocabulary. The subject of the study was the 15 students of SDIT Mentari Indonesia aged six years, grade 1. The dataset was also taken from the proceedings and any scholarly articles. Specifically, this study utilized a mixed research approach. The result indicates that the students could improve their English by playing the Pictionary game. Hence, it could be highlighted that the Pictionary game is one of the effective learning methods to increase students' English vocabulary.Keywords:  Early childhood, English, Pictionary game, VocabularyABSTRAK. Anak usia dini merupakan tahap yang paling kritis bagi anak dalam mengembangkan otaknya. Salah satu cara untuk mengembangkan otak anak adalah melalui pembelajaran bahasa. Bahasa Inggris adalah salah satu bahasa yang direkomendasikan untuk dipelajari. Pada usia dini, mempelajari kata-kata baru penting untuk memungkinkan anak-anak berbicara bahasa Inggris atau menulis kalimat bahasa Inggris. Ada banyak metode belajar mengajar yang menyenangkan untuk meningkatkan kosa kata siswa. Salah satunya adalah Pictionary. Penelitian ini bertujuan untuk menganalisis bagaimana Pictionary dapat digunakan sebagai alternatif untuk meningkatkan kosa kata siswa. Subjek penelitian adalah 15 siswa SDIT Mentari Indonesia yang berusia enam tahun, kelas 1. Data lain juga diambil dari prosiding dan artikel ilmiah. Secara khusus, penelitian ini menggunakan pendekatan penelitian campuran. Hasilnya menunjukkan bahwa siswa dapat meningkatkan bahasa Inggris mereka dengan memainkan permainan Pictionary. Oleh karena itu, dapat ditekankan bahwa permainan Pictionary adalah salah satu metode pembelajaran yang efektif untuk meningkatkan kosa kata bahasa Inggris siswa.Kata kunci: Anak usia dini, Bahasa Inggris, Pictionary, Kosa kata